2017
DOI: 10.1080/13697137.2017.1369513
|View full text |Cite
|
Sign up to set email alerts
|

The association of hyperuricemia and metabolic syndrome in Thai postmenopausal women

Abstract: There was a significant association of hyperuricemia and MS in Thai postmenopausal women. These two co-morbidities were common after menopause. When hyperuricemia is diagnosed, MS should be screened, prevented or treated to decrease cardiovascular disease in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Similar results were also reported by Techatraisak et al in post-menopausal Thai women. [ 22 ] Thus, the inconsistency among previous studies might be attributable to menopausal status. Several epidemiological studies have reported that SUA levels are higher in men than in women, [ 23 ] and the levels increased after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also reported by Techatraisak et al in post-menopausal Thai women. [ 22 ] Thus, the inconsistency among previous studies might be attributable to menopausal status. Several epidemiological studies have reported that SUA levels are higher in men than in women, [ 23 ] and the levels increased after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests a potentially causal role for urate in the pathogenesis of hypertension and atherosclerosis [28]. It was reported that sUA concentrations are higher in postmenopausal than in premenopausal women [30]. As far as we know, in postmenopausal women who did not receive estrogen hormone therapy, sUA concentration tended to increase due to a shortage of the uricosuric effect of estrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical HA was defined by a free androgen index (FAI) of >6.8 [15]. MetS was defined by the presence of ≥3 risk factors: (1) WC >80 cm; (2) hypertension >130/85 mmHg; (3) fasting plasma glucose (FPG) >6.1 mmol/L; (4) triglycerides (TG) >1.7 mmol/L; and (5) high-density lipoprotein (HDL-C) <1.3 mmol/L [16].…”
Section: Methodsmentioning
confidence: 99%